ORIENTASI PASAR : ANTESEDEN DAN KONSEKUENSI - Fransisca Mulyono (Bina Ekonomi, 2013)
Market orientation is a concept that is still proven efficacy because by applying this concept the company is able to sell products that suit the tastes and needs of its consumers. This is because there are three main activities in this concept, which is market intelligence generation,market intelligence dissemination and market responsiveness. Understanding the market orientation concept will be more profound when its antecendents and consequences are well understood. This paper discussed about the antecedents of market orientation, namely: senior management factors, interdepartmental dynamics and organizational systems. While the consequences of market orientation are organizational performance, customer Consequences, and innovation consequence.Keywords : market intelligence generation, market intelligence dissemination, market responsiveness, market orientation antecedents, market orientation consequences.Words : 6.044